Analisis Tren Teknologi Augmented Reality dalam Dunia Pendidikan - Aldian Yusup (Yayasan Banu Haji Samsudin, 2025)
The development of information and communication technology has driven a major transformation in the world of education, one of which is through the use of Augmented Reality (AR) technology. This technology combines virtual objects into the real world in real-time and enables an immersive, contextual, and enjoyable learning experience. This study aims to analyze the trend of AR utilization in Indonesian education over the past five years, and explore its relationship with the potential for utilizing digital technology to support the development of sustainable shopping tourism. This study uses a qualitative approach with a systematic literature study method on 10 relevant national and international scientific articles, published between 2019–2025. Data analysis was carried out using thematic analysis techniques to identify patterns of AR use, media development approaches, and their impact on learning outcomes. The results of the study show that AR has a significant positive impact on increasing learning motivation, understanding of complex concepts, and students' critical thinking skills. In addition, the trend of AR implementation also reflects cross-disciplinary integration, ranging from science education, engineering, health, to environmental literacy. When the reflection of the results of this study is drawn to the context of shopping tourism, it was found that the AR-based approach in education has great potential to be applied in supporting operational efficiency, enriching tourist experiences, and preserving local cultural values. This study suggests the integration of digital technology policies in education and tourism to promote sustainable development.